Effects of silver nanoparticles concentration on resistivity of PEDOT: PSS thin conductive films - Azmy, Udaimatunnoor; Ahmad, Zuraida; Ahmad Shahrim, Nur’Aishah Ahmad; Azman, Amelia Wong; Fajingbesi, Fawwaz Eniola (Mattingley Publishing Co., Inc., 2020)
In this study, the effects of silver (Ag) concentration on the electrical resistivity of poly(3,4thylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) films were investigated. The thin films were prepared by depositing Ag nanoparticles from aqueous dispersion using different concentrations: 2000 and 5000 ppm (parts per million) via syringe deposition method. Based on the results, it was found that, the film’s resistance reduced (from 1.49 kΩ to 0.52 kΩ) with the increase in Ag concentration (from 2000 to 5000 ppm). This is supported by the Field Emission Scanning Electron Microscopy (FESEM), in which the 5000 ppm Ag nanoparticles were well dispersed in PEDOT:PSS compared to 2000 ppm Ag nanoparticles. Additionally, the low resistivity of 5000 ppm Ag nanoparticles addition is corroborated with the presence of crystalline peak at 2θ of 38° and 78° evident by X-ray Diffractogram. Low resistivity of film leading to good electrical conductivity, hence, giving promising potential to be utilized in many applications such as in biomedical.